Design of geopolymer grouts: the effects of water content and mineral precursor. Issue 5 (4th May 2018) - Cherki El Idrissi, Anass; Roziere, Emmanuel; Loukili, Ahmed; Darson, Sabine
Abstract : Geopolymers have gained much interest recently as a promising alternative to cementitious materials in some applications. However, research is still needed to use this technology for soil reinforcement grouts. The specifications of grouts mainly consist in rheological properties, strength and permeability. Grouting actually requires a low viscosity, and thus higher water content. The influence of relatively high water content on the other properties of the material, i.e. strength and microstructure, has been investigated. This effect highly depends on the concentration of the activator (sodium silicate solution) and the precursor (metakaolin, fly ash or blast furnace slag) associated with the activator. This paper deals with the main effects of high water content on the microstructure and mechanical properties of the materials, looking at physical and chemical aspects. Scanning electron microscopy and chemical phase analysis were used to highlight the nuances that are related to the precursors used, especially regarding the microstructure and kinetics of the geopolymerisation process.